Análisis exploratorio del nivel de aplicación de herramientas de gestión de operaciones en la administración de cementerios y funerarias (2019)
Cemeteries and funeral home industry is one of the biggest sectors worldwide. Its services are increasingly demanded and it is necessary to implement improvement strategies that allow to ensure efficiency and keep customer service indicators. This project aims to assess the current implementation level of the most known operations management tools, applied to the administration of cemeteries and funeral homes at Barranquilla, Colombia, proposing improvement strategies that lead to efficient operational results. The methodology is composed of three phases that include the characterization of operational conditions at local cemeteries and funeral homes, a survey, and the identification of improvement opportunities, taking into account current implementation levels.